2010
DOI: 10.4314/jae.v13i1.53884
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Improved Rice Varieties among Small- Scale Farmers in Katcha Local Government Area of Niger State, Nigeria

Abstract: The study broadly aims at providing information on the adoption of improved rice varieties among small-scale farmers in Katcha Local Government Area of Niger state, Nigeria. The study was conducted in 2007 cropping season. Data were generated from a sample of 100 farmers using questionnaire. Results indicated a high rate of awareness of improved rice varieties. The main sources of information were radio and extension agents. The major reasons for nonadoption of improved rice varieties are that they are expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(3 reference statements)
0
3
2
Order By: Relevance
“…The finding implies that the respondents in study area rely more on extension workers as a major source of sourcing information (Figure 1) on improved rice production technologies. This finding differs with Shegun and Adun (2002) and Jirgi (2009) who reported that the greatest key source of information was radio with 43% followed by neighbors (29%) and extension agents (28%). According to Jirgi et al (2009) among rice farmers in Niger State, Nigeria 56% of the farmers received information through the radio, 28% through extension agents, 10% through television and pamphlet 6%.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 88%
See 1 more Smart Citation
“…The finding implies that the respondents in study area rely more on extension workers as a major source of sourcing information (Figure 1) on improved rice production technologies. This finding differs with Shegun and Adun (2002) and Jirgi (2009) who reported that the greatest key source of information was radio with 43% followed by neighbors (29%) and extension agents (28%). According to Jirgi et al (2009) among rice farmers in Niger State, Nigeria 56% of the farmers received information through the radio, 28% through extension agents, 10% through television and pamphlet 6%.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 88%
“…This finding differs with Shegun and Adun (2002) and Jirgi (2009) who reported that the greatest key source of information was radio with 43% followed by neighbors (29%) and extension agents (28%). According to Jirgi et al (2009) among rice farmers in Niger State, Nigeria 56% of the farmers received information through the radio, 28% through extension agents, 10% through television and pamphlet 6%. Fadiji et al (2005) reported that the major sources of extension information among farmers in rural Nigeria were extension agents, radio and other farmers.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 88%
“…This coupled with population pressure has resulted in food insecurity. Jirgi et al (2007) Cooperative societies and self-help groups are also major players in this respect. Other initiatives included theSmall -Scale Industries Credit Guarantee Scheme (SSICGS), the Nigerian Commercial Banks and Agricultural Credit Guarantee Scheme Fund (ACGSF), the Commercial Agricultural Credit Scheme (CACS), Nigeria Initiative-based risk sharing system for agricultural lending (NIRSAL), Agricultural Credit Support Scheme (ACSS) and the Anchor Borrower's Programme (ABP).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is from the family Poaceae, Genus Oryza and species sativa L. and glaberrima. The crop was introduced to West Africa in the early 19th century (Jirgi et al, 2009). Rice (Oryza sativa) is the most important staple food for about half of the human race and one-third of the world population depend on rice for about 50% of their daily calorie intake (Food and Agricultural Organization -FAO, 2011;National Cereals Research Institute -NCRI, 2010).…”
Section: Introductionmentioning
confidence: 99%